Survey: Agent-based Middlewares for Context Awareness - Sahli, Nabil (Electronic Communications of the EASST, 2008)
In the last few years, many middlewares for context awareness have claimed to be agent-based. In this paper, we make a survey on the most known frameworks. We classify them according to their level of conformity to the agent paradigm and we discuss the usefulness of agents in these frameworks. Based on this survey, we enumerate several advantages of using agents in context-aware middlewares and give illustrative examples. We also point to the weakness of existing frameworks and identify challenges to be addressed.